Mechanical Behavior Dependence on Geotextiles Interweave Configuration Used in Coastal Restoration - WAKAYAMA, Shuichi; CANTO-PINTO, Jorge Carlos; PEREZ-PACHECO, Emilio; RIOS-SOBERANIS, Carlos Rolando; SAKAI, Takenobu (Advanced Experimental Mechanics, 2024)
Geotubes are the most used technology for coastal recovery due to erosion and, because of the lower price and easier installation, geotextile tube systems can be good alternatives for hydraulic and coastal structures. Geotubes can suffer damage due to cuts in fibers and other components, formation of holes, abrasion originating a reduction in mechanical resistance. On the other hand, when filled in-situ by hydraulic pumping is assumed that tensile stresses act directionally due to the hydraulic pressure and the tensile force in the geosynthetic tube. Therefore, it is important to understand the mechanical behavior as well as to identify the stages during the damage process. A mechanical vital role is sustained by the textile architecture and configuration since stresses will be transferred along the textiles. This paper exhibits the full mechanical characterization of two geotextiles made of polyethilenethereftalate (PET) and polypropylene (PP) respectively, both with different interweave architecture. Results found that textile geometry is crucial for bearing stresses and depend on the acting direction. Acoustic emission technique was employed to identify the mechanism of failure that supported the mechanical characterization findings.